The usage of mercury ingredients in cosmetic products: an analysis from fiqh perspectives - Hamzah, Nur Arifah; Mat Jubri @ Shamsuddin, Mustafa (2023)
This research problem is to identify the forms and characteristics of mercury that have been used in cosmetic products as well as its health effects from the exposure of it. Besides, this research will analyse the prohibition based on the Qawaid Fiqhiyyah, Al-Quran and Sunnah, and also from Maqasid Al-Syariah with the criteria of prohibition related to the mercury usage. This research methodology is using the qualitative method. The researchers did library research, especially recent studies from journal articles and databases. Furthermore, this research conducted interviews with three respondents according to their expertise. They are expertise in biotechnology which is closely related with this research about mercury in cosmetics, dermatology which is related to mercury's health effects, and fiqh and usul expertise to understand the rule of mercury usage in cosmetic products. The result demonstrates the mercury usage in products is prohibited (Harām) as it will harm the consumers health and it will change the creation of Allah by changing their natural skin colour temporarily. To conclude that, it is important for us as a Muslim to gain knowledge about this matter because it is related to health that we must take care of.